The Meaning of the Phrase dib·ber ‘ā·la·yiḵ rā·‘āh in Jeremiah 11:17 : An Exegetical Study - Gosal, Fellix; Mantiri, Mauritz Ramber Devlen (12th International Scholars Conference 2025, 2026)
The phrase dib·ber ‘ā·la·yiḵ rā·‘āh in Jeremiah 11:17 is the primary focus of this research. The verb dib·ber, in its Piel form, carries an intensive meaning, indicating that God "forcefully spoke" or "decisively ordained" disaster upon Israel and Judah. This study employs an in-depth exegetical approach to address key questions: Why did God, who had a nurturing relationship with these nations, take such drastic and intensive action? What specific factors led to this severe judgment?By analyzing the historical, literary, and theological contexts of Jeremiah 11:17 and related passages, this research aims to provide a more nuanced understanding of divine justice. We will explore the covenantal relationship between God and Israel, highlighting how their persistent idolatry and disregard for divine law constituted a profound betrayal. The intensive nature of the verb dib·ber underscores that God's decision was not impulsive but a deliberate and final response to centuries of rebellion. The findings of this study are intended to enrich theological discourse on God's nature and aid in interpreting challenging prophetic texts, offering insights into the complex balance between divine grace and righteous judgment. The research posits that God's justice is not arbitrary but is a direct consequence of His unwavering commitment to His covenant and His holy character.